THE DEVELOPMENT OF SCIENTIFIC WRITING SKILLS IN PESANTREN: A COMPARATIVE ANALYSIS ON MA’HAD ALY SUKOREJO SITUBONDO AND MA’HAD ALY MANGGISAN WONOSOBO - Muhamad Murtadlo (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
This paper will examine the scientific writing skills in the context of pesantren. The pesantren has a long scientific history in Indonesia, unfortunately, it has not been accompanied by a strong tradition of scientific writing. The research question formulated is to figure out what causes the tradition of scientific writing in pesantren is not that strong. To find out the answer, this study will use a qualitative approach by raising two pesantren cases that organize ma’had aly education, namely the Ma’had Aly Sukorejo Situbondo and the Ma’had Aly Manggisan Wonosobo. This study found that the reason why the tradition of writing in pesantren is not that strong is due to the lack of scientific writing being introduced in pesantren. Eventhough, they have been introduced to the scientific tradition and academic culture in deciding various socio-religious issues. This study recommends the need for a pesantren breakthrough in the developing of scientific writing culture.